Debye screening in generalized quantum electrodynamics - Bonin, C. A.; Gracia, G. B. de [UNESP]; Nogueira, A. A.; Pimentel, B. M. [UNESP] (World Scientific Publ Co Pte Ltd, 2020)
In this work we study the Higgs mechanism and the Debye shielding for the Bopp-Podolsky theory of electrodynamics. We find that not only the massless sector of the Podolsky theory acquires a mass in both these phenomena, but also that its massive sector has its mass changed. Besides exploring the behavior of the screened potentials, we find a peculiar temperature T-P associated with the Podolsky length.
Keywords: Finite temperature; Debye screening